Bibliometric analysis of NMDA receptors: 2015–2024 - Liu, Yunsheng; Jia, Yanyan; Kou, Zengwei (Frontiers in Pharmacology, 2025)
NMDA receptors, a subtype of ionotropic glutamate receptors, play pivotal roles in the brain by mediating synaptic signal transduction, facilitating intercellular communication, and shaping neural circuits, thereby serving as molecular switches for learning and memory. Since its discovery and isolation in the 1960s, NMDA receptors have remained a focal point of research in neuroscience. The past decade has witnessed a large number of high-quality studies on the biophysical properties, three-dimensional structure, and pathophysiological functions of NMDA receptors. In this study, we employed bibliometric methods to analyze publications from 2015 to 2024, visualizing research hotspots, trends, and key milestones of NMDA receptors. Additionally, we also identified the leading researchers, institutions, and countries that contributed to this area. Our findings provide a comprehensive overview of recent NMDA receptor research, which will help readers understand the trends and influence in this field.